استخدام عزلات محلية من الفطر Trichoderma ضد أطوار مختلفة من نيماتودا تعقد الجذور Meloidogyne incognita مخبرياً - ألوف, ندى; يازجي, ميساء; قسّام, رامي (Latakia University Journal -Biological Sciences Series, 2019)
تـم تقييم فاعلية (7) عزلات محلية من الفطر Trichoderma ضد نيماتودا تعقد الجذور Root Knot Nematode (RKN) Meloidogyne incognita Goeldi مخبرياً, عزلتان منها تتبع النوع Trichoderma longibrachiatum Rifai و(4) عزلات تتبع للنوعPers. ex s.f. Gray Trichoderma viride وعزلة واحدة تتبع النوعTrichoderma harzianum Rifai معزولة من تربة وجذور نباتات بندورة مصابة بنيماتودا (RKN) في ظروف الزراعة المحمية في الساحل السوري, بالمقارنة مع فاعلية المستحضر التجاري (Biocont) والذي مادته الفعالة أبواغ الفطرTrichoderma harzianum والمستخدم ضد أطوار نيماتودا (RKN). وقد دلت النتائج على قدرة جميع العزلات المحلية على التطفل على بعض أطوار النيماتودا (RKN). حيث بلغت النسب المئوية لتطفل الأنواع السابقة من العزلات المحلية على بيوض النيماتودا (RKN) داخل كتل البيض, (37.86%),(37.36%) و(43.70%) على التوالي وهي أعلى من النسبة المئوية لتطفل المستحضر التجاري (26.20%) على النيماتودا المدروسة. كما ارتفعت معدلات تطفل العزلات ذاتها على بيض النيماتودا المحرر من كتل البيض والتي بلغت (71.47%),(60.43%) و(71.25%) على التوالي مقارنةً مع المستحضر التجاري (40.20%), ومن جهة أخرى أظهرت جميع العزلات المحلية قدرة عالية على التطفل على إناث النيماتودا حيث بلغت نسبة تطفل العزلة المحلية الأقوى T. harzianum (90.56%) مقارنةً مع تطفل المستحضر التجاري (63.22%), كما ثبطت العزلة الأقوى فقس بيوض النيماتودا (RKN) حيث بلغ معدل الفقس (5.75%) وهي نسبة منخفضة جداً مقارنةً مع المستحضر التجاري والشاهد والتي بلغت (41.50%),(51%) على التوالي. This paper evaluates the efficacy of seven local isolates of the fungi Trichoderma against the root-Knot nematode (RKN) Meloidogyne incognita Goeldi in laboratory. 2 of them belong to Trichoderma longibrachiatum Rifai, 4 belong to Trichoderma viride Pers. ex s.f. Gray, and 1 to Trichoderma harzianum Rifai. They were isolated from (RKN) infected soil and roots of tomato under greenhouse conditions in the Syrian coast. They were compared with the efficacy of commercial product (Biocont) which contains spores of T. harzianum against all stages of (RKN) which infects tomato's plant. Results showed that all local isolates had a potential virulence to parasitize some stages of (RKN). The percentage of the local isolates parasitism of Trichoderma, (T.l),(T.v) and (T.h), on eggs inside egg masses was about (37.86%),(37.36%) and (43.70%) respectively. It was higher than commercial product parasitism (26.20%) on studied nematodes. Parasitism rate of the same previous isolates on freed eggs from egg masses was (71.47%), (60.43%) and (71.25%), respectively. It was clearly higher than the commercial product parasitism (40.20%). Moreover, the whole local isolates showed high capacity of parasitism on female's nematodes: it reached in the strongest local isolate (T.h) to (90.56%) compared with the commercial product parasitism (63.22%). This isolate damped eggs hatching of (RKN) to (5.75%). It was very low compared with commercial product and control, which reaches (41.50%) and (51%), respectively.